Intensification of microbial exopolysaccharide ethapolan synthesis on the mixture of energy-excessive substrates - Voronenko, Andryi; Pirog, Tatiana (My University, 2021)
Introduction. The cultivation conditions of Acinetobacter sp. IMV B-7005, providing maximum synthesis of exopolysaccharide (EPS) ethapolan on the mixture of ethanol and sunflower oil were studied, as well as the possibility of replacing refined oil in the mixture with ethanol on a waste one was demonstrated. Materials and methods. Strain IMV B-7005 was grown in liquid mineral media, containing the mixture of ethanol and sunflower oil of various quality, as well as appropriate monosubstrates. The optimal molar ratio of the concentrations of substrates in the mixture was calculated theoretically according to Babel’s concept. The EPS concentration was determined gravimetrically after precipitation with isopropanol, the EPS-synthesizing ability – as the ratio of the EPS concentration to the concentration of biomass and expressed in g EPS/g biomass. Results and discussion. The highest rates of ethapolan synthesis were observed with the molar ratio of concentrations of ethanol and refined sunflower oil in the mixture of 1:0.056, as close as possible to the theoretically calculated (1:0.076), and the use of inoculum grown on ethanol. Further increasing of the concentrations of ethanol and oil led to a decrease in pH of the culture fluid to a suboptimal level for the EPS synthesis (4.5-4.8). To ensure the synthesis of ethapolan on a medium with high concentrations of ethanol (4%) and oil (1.2%) ammonium nitrate was replaced with an equimolar amount of nitrogen KNO3 (0.8 g/l), which is transported into cells by the symport with proton; fractional introduction of substrates in five equal portions during cultivation was carried out and was increased the concentration of Mg2+ cations, which are one of the activators of acetyl-CoA synthetase in Acinetobacter sp. IMV B-7005 affecting the enzymatic activity of systems responsible for the catabolism of fatty acids. Under such cultivation conditions, regardless of the type of used sunflower oil (refined or mixed waste) in the mixture with ethanol, the concentration of ethapolan reached 13.5-16.0 g/l, and EPS-synthesizing ability – 3.1-3.7 g EPS/g of biomass, which were respectively 3.2-3.8 and 1.6-1.9 times higher than before optimization. Conclusions. Based on determining the optimal molar ratio of monosubstrate concentrations in the mixture, modification of the medium composition (replacement of ammonium nitrate with potassium nitrate, increasing the content of magnesium cations, replacement of refined oil on a mixed waste one) and fractional addition of substrates the possibility of intensification of ethapolan synthesis on the mixture of energy-excessive substrates (ethanol and sunflower oil) was established.
Keywords: змішані субстрати; біосинтез; екзополісахариди; етаполан; кафедра біотехнології і мікробіології; Acinetobacter sp. ІМВ В-7005; mixed substrates; biosynthesis; exopolysaccharides; ethapolan